Identificación de la entomofauna en el transecto n° 4 parte a, cantón Pujilí, provincia Cotopaxi, 2016-2017. - Mejía Candelejo, José Humberto (2017)
The purpose of this research was to study insects because they are an important biodiversity asset. Although, they are not given the importance they deserve. The main aim of this project was to identify the "entomofauna" in the transect, 4 part A, at Pujilí Canton, Cotopaxi Province during 2016 – 2017 period. The project was divided into three stages; the first one was to collect species from natural fall traps, each of them with four samples. The second stage was to classify and conserve, using the dichotomy clues to identify and saving the samples for further studies. The last stage was to determine the biodiversity and abundance in the transect using the Shannon Index applied in the La Esperanza Parish, Yungañan Area, Pujilí Canton where the study zone was divided in transects which total area is one hectare located at 79°05,544''S longitude, 0°57,384''W latitude at 1378 m.a.s.l. A total of 858 individuals were collected, considering only the insect order, which means larvae and nymphs were not counted. A total of 42 families were identified proving that there are 13 families with more than ten individuals in each one which prevails, where the Formicidae Family is the one with more individuals overcoming all families with about 190 individuals within the transect. According to the Shanon Index, the 858 individuals collected represent 0.7169; this measure can determine a low abundant area which might be due to the vegetation type and the inequitable distribution of individuals in the study area.